PHARYNGOMYCOSIS IN CHILDREN - Sodiqova M. B.; Ismatova K. A. (Modern American Journals, 2025)
Chronic pharyngitis is one of the most common pathologies of the pharynx and can occur both as an independent disease and be a manifestation of pathology of other organs and systems of the body. To date, many methods of treating this condition have been proposed, but, in some cases, the effectiveness of the therapy remains low. Among the reasons for the lack of effect may be acidosis of the mucous membrane of the pharynx associated with gastroesophageal reflux disease (GERD), which causes changes that are difficult to treat with conventional therapy. According to various authors, the prevalence of GERD reaches 60%. At the same time, the addition of a fungal infection makes the patient's treatment even more difficult. It has been established that in 29 - 44.6% of patients, chronic pharyngitis of various etiologies is combined with a fungal lesion of the pharynx and the number of such patients does not decrease. In addition, it has been proven that atrophic changes in the mucous membrane of the pharynx contribute to the adhesion and colonization of fungal biota on it. Along with this, there is no data on the relationship between the level of acid-base balance (pH) of the mucous membrane of the pharynx and the presence of fungal flora on it in chronic pharyngitis.